Study and analysis of the use of restriction and their function in the novel (Najran Nabash) by Mahsa Moheb Ali - Salman, Jassim; ALFAILY, EVAN (Al-Adab Journal, 2024)
Mehsa Mohib Ali's novel "Don't Worry" is one of the most reliable novels in Persian literature and is full of excellent technical and rhetorical data and the fluency of the Persian language. Use an adverb of a word or group or sentence in Persian and it is in the form of adjective, place, quantity, state, quality and emphasis, and sometimes replace the noun. Adverb in Persian language is one of the issues that has not been properly studied in the studies of literature and grammar. Adverbs are discussed and developed from several grammatical schools such as (classical school, formalism school, constructivist grammar school, historical grammar school and new school). Semanticist) all these schools have had different form and analysis and development than others and, in this article, don't worry as an adverb from the derivational and derivational areas and its role in the novel, and the way the adverb plays a new meaning and role in sentences and arrangement.